2021
DOI: 10.4012/dmj.2021-010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in-office bleaching materials with different pH on the surface topography of bovine enamel

Abstract: This study evaluated the alterations of surface topography of the bovine enamel caused by different pH of in-office bleaching agents. 23% H2O2 with pH 5.5, 7.0 and 8.5 were applied on the bovine tooth specimens (n=10) and photo-irradiated for 10 min. The bleaching procedure was repeated three times and specimens were subjected to linear surface roughness (Ra) and Vickers microhardness test (VHN) at baseline and after three consecutive applications. The morphological alterations were observed before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
1
10
0
2
Order By: Relevance
“…Although the acidic nature of CP (pH 6.5) caused some dissolution of the precipitated minerals from the enamel surface, SEM analysis revealed no changes in enamel porosity after bleaching, which is in line with other studies [9][10][11]. Possible explanations for the conflicting results [8,12] are the differences in the bleaching material with less pH levels than carbamide peroxide, and the differences in the methodology. We applied carbamide peroxide on SDF-treated carious lesions with evidently less porous areas than the demineralized enamel surface.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although the acidic nature of CP (pH 6.5) caused some dissolution of the precipitated minerals from the enamel surface, SEM analysis revealed no changes in enamel porosity after bleaching, which is in line with other studies [9][10][11]. Possible explanations for the conflicting results [8,12] are the differences in the bleaching material with less pH levels than carbamide peroxide, and the differences in the methodology. We applied carbamide peroxide on SDF-treated carious lesions with evidently less porous areas than the demineralized enamel surface.…”
Section: Discussionsupporting
confidence: 85%
“…It is proposed that dental bleaching might help ameliorate these discolorations [7]. Many studies with controversial results have assessed the effect of bleaching products on mineral content and physical properties of the tooth surface [8][9][10][11][12]. Since the acidic nature of the whitening products raised concerns regarding the possibility of alteration in the enamel composition, fluoridated dental bleaching products were introduced to the market [13].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction between peroxide and organic molecules on the surface or in the subsurface of the enamel could cause morphological changes in the enamel. When teeth are exposed to peroxide, an initial process of enamel demineralization occurs, resulting in the loss of calcium in the teeth [44]. Apart from the dentist-supervised carbamide peroxide group and the OTC groups, the enamel specimens in this study were also exposed to citric acid and distilled water to better understand the effect of these whitening agents on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…The same considerations follow through to the issue of surface microhardness. Several in vitro studies have reported that changes in microhardness are directly correlated to the degradation of the inorganic and organic components of the tooth surface [ 17 , 18 , 19 ], mostly due to the actions of free radicals. The present results for HP and CP causing reduced surface microhardness are consistent with prior studies.…”
Section: Discussionmentioning
confidence: 99%